Desenvolvimento e avaliação de uma intervenção no sistema familiar de adolescentes com baixo desempenho escolar - Silva, Magda Pozzobon (Universidade do Vale do Rio dos Sinos, 2016)
Considering the influence of family interactions in school performance, this dissertation sought to develop and evaluate a multifamily intervention involving families and teenage students with a history of low academic performance in two public elementary schools in the network of São Leopoldo/RS. Two studies were derived: the first is an experience report about the intervention carried out in six meetings, which had a duration of 90 minutes, with activities that aimed at increasing communication, affective interaction and autonomy in the members of the system. The use of expressive resources as mediation tools promoted a playful, relaxed environment and complicity, which facilitated the expression of emotions, inciting the insight and leading to changes in the family system. The second study was empirical, of mixed approach with pre-experimental design with pre and post-test with this group, and evaluated the results of the proposed actions in relation to the family support and academic achievement. The qualitative content analysis pointed to improved dialogue between parents and children, greater family union and development of behaviors related to schedules, rules and limits, praise, autonomy and commitment with studying. The school grades were improved and all students were approved. Together, the data shows the importance of family systems intervention to help parents understand the importance of their participation in the teaching-learning process of children and to promote closer ties between the family and school system, in the pursuit of building spaces for reflection on educational practices in both contexts.
Keywords: Intervenção multifamiliar; Desempenho escolar; Recursos expressivos; Multi-family; School performance; Expressive resources; ACCNPQ::Ciências Humanas::Psicologia